PEMIKIRAN IBNU SINA (RELIGIUS-RASIONAL) TENTANG PENDIDIKAN DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM KONTEMPORER - Rika Amalia (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
Study This aim For know Ibn Sina's thoughts about education and its relevance with contemporary Islamic educatio . Concepts according to Islamic education characters Muslims, of course become attention so that, Islamic education is able dominate pattern education in Indonesia. So that Muslims can face the times, especially in aspects education. Method research used in study This is analysis descriptive qualitative. As for the type research used is study bibliography (library research) use obtain appropriate facts in obtain base theory or framework think to the problems studied. Data source from study This is books nor other literature in the form of journals or article. Data analysis technique used is analysis content (content analysis). Result of study This show that thinking Ibn Sina's Islamic education has relevance with contemporary and very still Islamic education Can implemented at this time. Related specials _ with development potency physical, intellectual, and mental character participant teach and apply draft the ideal educator who still is relevant For implemented in this era. Keywords : _ Ibn Sina's Educational Thought , Contemporary Islamic Education